Dapatkah Literasi Keuangan Dan Pemahaman Akuntansi Menghasilkan Kualitas Laporan Keuangan Puskemas? - Fitriani; Syamsul Ridjal; La Ode Sumail (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2022)
The purpose of this research is to investigate the quality of financial reports mediated by Accounting Information Systems. The sampling method used purposive sampling with consideration of employees who have accounting knowledge and competence as much as 98 employees. The analytical equipment used is WarpPLS 7.0. Financial literacy has a positive and significant effect on the quality of financial statements. Accounting understanding has a positive and significant effect on financial statements. Financial literacy has a positive and significant effect on Accounting Information Systems. The Accounting Information System variable has a positive and significant effect on the quality of financial reports. Understanding of accounting has a positive and significant effect on Accounting Information Systems. Then, the Accounting Information System plays a positive and significant role in mediating the relationship between financial literacy and accounting understanding with the quality of financial reports at the Regional Public Service Agency Public Health Center in Makassar City.